2018
DOI: 10.3389/fpls.2018.01569
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Approach to Analyze Systemic Jasmonate Accumulation in Individual Leaves of Arabidopsis Rosettes Upon Wounding

Abstract: Phytohormones, especially jasmonates, are known to be mediators of the plant responses to wounding and herbivore feeding. Their role in such stress responses has been largely studied locally in treated leaves. However, less is known about the induced systemic distribution of phytohormone signals upon these kinds of stresses. Here, a holistic approach was performed in order to investigate the systemic phytohormone pattern in the rosette of Arabidopsis thaliana after herbivore-related wounding. Levels of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 39 publications
0
35
1
Order By: Relevance
“…Literature is replete with publications on oxylipins as signalling molecules in plant defence mechanisms and many studies provide evidence for a strong interplay between phytohormones [3,26,39,[49][50][51][52][53][54][55][56][57]. JA and its derivatives, known as jasmonates, are the best-characterised LOX-derived metabolites as they accumulate quickly in damaged plants [2,36,58].…”
Section: Effectiveness Of Pos As Signalling Molecules In Plant Defencmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature is replete with publications on oxylipins as signalling molecules in plant defence mechanisms and many studies provide evidence for a strong interplay between phytohormones [3,26,39,[49][50][51][52][53][54][55][56][57]. JA and its derivatives, known as jasmonates, are the best-characterised LOX-derived metabolites as they accumulate quickly in damaged plants [2,36,58].…”
Section: Effectiveness Of Pos As Signalling Molecules In Plant Defencmentioning
confidence: 99%
“…Adapted from [4,16,17]. rapidly (<5 min) in leaves distal to wounding sites [30,50,61]. Interestingly, this long-distance signalling does not seem to involve the direct movement of hormones and could involve much faster systems: electrical coupling or ROS and Ca 2 +-mediated waves, 'trio signalling' [62,63].…”
Section: Effectiveness Of Pos As Signalling Molecules In Plant Defencmentioning
confidence: 99%
“…, 2012; Heyer et al . , 2018; Schulze et al , 2019). Therefore, it is necessary to re‐quantify JA concentrations in these plants as both wounding and SYS treatment caused JA accumulation in tomato leaves as demonstrated previously (Doares et al .…”
Section: Pro‐sys Mrnamentioning
confidence: 99%
“…(2013) and Heyer et al . (2018), who reported that OPDA concentrations increased only in local tissues but not in systemic leaves after continuous wounding. This suggested that the systemic elevation of JA is not a result of de novo biosynthesis, but rather of transport between the leaves, as shown in N. tabacum plants (Sato et al , 2011).…”
Section: Jasmonatesmentioning
confidence: 99%
“…Phytohormone analysis was performed by LC-MS/MS as in Heyer et al . [ 87 ] on an Agilent 1260 series HPLC system (Agilent Technologies) with the modification that a tandem mass spectrometer QTRAP 6500 (SCIEX, Darmstadt, Germany) was used. Details of the instrument parameters and response factors for quantification can be found in S1 Table .…”
Section: Methodsmentioning
confidence: 99%